Design of VDC photovoltaic and wind power hybrid system using smart relay - Marhidayu Bt. Mohd Raid (School of Electrical System Engineering, University Malaysia Perlis, 2011)
This project is developed to produce 24 V DC by photovoltaic and wind power hybrid system using smart relay. The smart relay SR3 B261JD from Schneider Electric is used to operate as controller that will choose the highest voltage produced between photovoltaic and wind